Targeting DNA Damage Response Pathway in Ovarian Clear Cell Carcinoma - Wong, Oscar G. W.; Li, Jing; Cheung, Annie N. Y. (Frontiers in Oncology, 2021)
Ovarian clear cell carcinoma (OCCC) is one of the major types of ovarian cancer and is of higher relative prevalence in Asians. It also shows higher possibility of resistance to cisplatin-based chemotherapy leading to poor prognosis. This may be attributed to the relative lack of mutations and aberrations in homologous recombination associated genes which are crucial in DNA damage response (DDR), such as BRCA1, BRCA2, p53, RAD51, and genes in the Fanconi anemia pathway. On the other hand, OCCC is characterized by a number of genetic defects rendering it vulnerable to DDR targeting therapy which is emerging as a potent treatment strategy for various cancer types. Mutations of ARID1A, PIK3CA, PTEN and catenin beta 1 (CTNNB1) as well as overexpression of transcription factor hepatocyte nuclear factor-1β (HNF-1β) and microsatellite instability are common in OCCC. Of particular note is the loss-of-function mutations in ARID1A, which is found in approximately 50% of OCCC. ARID1A is crucial for processing of DNA double-strand break (DSB) and for sustaining DNA damage signaling, rendering ARID1A deﬁcient cells prone to impaired DNA damage checkpoint regulation and hence sensitive to poly ADP ribose polymerase (PARP) inhibitors. However, while preclinical studies have demonstrated the possibility to exploit DDR deficiency in OCCC for therapeutic purpose, progress in clinical application is lagging. In this review, we will recapitulate the preclinical studies supporting the potential of DDR targeting in OCCC treatment, with emphasis on the role of ARID1A in DDR. Companion diagnostic tests (CDx) for predicting susceptibility to PARP inhibitors are rapidly being developed for solid tumours including ovarian cancers and may readily be applicable on OCCC. The potential of various available DDR targeting drugs for treating OCCC by drawing analogies with other solid tumors sharing similar genetic characteristics with OCCC will also be discussed.